Obietnice i wymówki: Derrida i aporia podmiotowości - Agata Bielik-Robson (Przestrzenie Teorii)
The aim of this essay is mainly critical: it intends to demonstrate that despite all the promises to give account of a "deconstructive subjectivity," Derrida failed to do so, postponing the moment of positive delivery and providing in the end only excuses. This charge relies on the thesis that Derrida - again, despite his overt declarations - proved unable to rethink critically the concept of narcissism which he himself saw as crucial for the future philosophical understanding of subjectivity. And although Derrida draws the concept of narcissism from the writings of Freud, it can be nonetheless easily shown that the meaning he attaches to this notion is much older: its true source appears to be Hegel's famous critique of the beautiful soul. My purpose here will be to show that what Derrida calls the aporia of narcissism is, in fact, nothing more than the deconstructive version of the Hegelian dilemma of the beautiful soul - and, theoretically speaking, a rather "defunct" one, for it explicitly prohibits any dialectical procedure that could lead us out of this aporetic predicament.